A Critical Review of Scottish Renewable and Low Carbon Energy Policy - Wood, Geoffrey; Baker, Keith (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book offers comprehensive coverage of current energy policy in Scotland focussing on non-fossil fuel energy options: renewables, nuclear power and energy efficiency. Covering issues of policy and practice, planning, legislation and regulation of a range of sustainable energy technologies in the context of devolved government, key experts explore these issues in terms of the ongoing Scottish independence debate, Brexit and further devolution in this vitally important and timely book. The book emphasises two further distinctive areas: constitutional change and the role of sub-national authorities in renewable and low carbon energy policy and practice. The clear focus on renewable and low carbon energy policy and practice and sub-national authority level of governance of energy means that it will be of particular relevance as a case study for those countries either in the process of deploying renewable and/or low carbon energy technologies or looking to do so. The authors discuss the many lessons to be learnt from the Scottish and UK experience. By providing a critical analysis of the subject, this book will be an invaluable reference to students, practitioners and decision-makers interested in renewable and low carbon energy transitions, energy planning and policy.
Keywords: Social sciences.; Renewable energy resources.; Energy policy.; Energy and state.; Great Britain -- Politics and government.; Renewable energy sources.; Alternate energy sources.; Green energy industries.; Environmental policy.; elektronické knihy; electronic books